The Impact of Online Corporate Reporting Quality on Analyst Following and Properties of Their EPS Forecasts - Ahmed Saleh; Clare B. Roberts (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This paper investigates the impact of the quality of online corporate reporting (OCR) by UK listed firms on analyst behavior. Using a proposed new OCR index, we find that higher quality of OCR is related to increased analyst following. Additionally, we find that the main OCR component that drives analyst following is financial information content. However, we find no association between the quality of OCR and properties of analyst EPS forecasts as proxied by error in analyst EPS forecasts, dispersion in analyst EPS forecasts and common uncertainty in analyst information environment. We also investigate the direction of causality between OCR quality and analyst following and find that the later has no impact on the first. Furthermore, we find no evidence that herding behavior by financial analysts in the UK has interrupted the association between the quality of OCR and forecast properties. Our results contribute to the understanding of the role of analysts as information intermediaries in providing information to investors.
Keywords: M41; 650; Financial analysts; disclosure quality; online corporate reporting; analyst behavior; analyst herding